2021
DOI: 10.1210/clinem/dgab096
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality Risk in Patients With Primary and Secondary Adrenal Insufficiency

Abstract: Context Mortality data in patients with adrenal insufficiency are inconsistent, possibly due to temporal and geographical differences between patients and their reference populations. Objective To compare mortality risk and causes of death in adrenal insufficiency with an individually-matched reference population. Design Retrospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…Early diagnosis of ICI-induced hypopituitarism is clinically important for the initiation of appropriate treatment and prevention of adrenal crisis, which has a fatal clinical course [ 11 , 12 ]. A latest survey revealed that adrenal crisis accounted for 10% of all deaths of patients with adrenal insufficiency [ 13 ]. Hydrocortisone replacement therapy can be used to treat ICI-induced hypopituitarism, and ICI therapy can be resumed once the patient’s condition stabilizes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of ICI-induced hypopituitarism is clinically important for the initiation of appropriate treatment and prevention of adrenal crisis, which has a fatal clinical course [ 11 , 12 ]. A latest survey revealed that adrenal crisis accounted for 10% of all deaths of patients with adrenal insufficiency [ 13 ]. Hydrocortisone replacement therapy can be used to treat ICI-induced hypopituitarism, and ICI therapy can be resumed once the patient’s condition stabilizes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even under optimal glucocorticoid replacement, patients affected by PAI show decreased quality of life ( 125 ) and increased mortality, with infections and cardiovascular and respiratory diseases as leading causes of death ( 126 128 ). In patients with hypopituitarism, AI has been associated with increased risk of death ( 129 ), and among patients with AI, those with SAI showed higher mortality ( 130 ); however, this result has not been confirmed by a more recent study ( 127 ). Cardiovascular mortality in patients with AI has been reported to be higher in female patients ( 128 ) and is associated with former comorbidities ( 131 ).…”
Section: Discussionmentioning
confidence: 85%
“…Main causes of death were cancer, cardiovascular and infectious disease, the latter being possibly driven by inadequate glucocorticoid exposure, especially at times of intercurrent illness ( 10 ). With only limited studies available, the mortality rate from AC is estimated to be 0.3-0.5/100 patient years ( 2 , 5 , 6 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%